2007
DOI: 10.1021/bm700697a
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine Analogues Bind Human Serum Albumin

Abstract: Polyamine analogues show antitumor activity in experimental models and their ability to alter activity of cytotoxic chemotherapeutic agents in breast cancer is well documented. Association of polyamines with nucleic acids and protein is included in their mechanism of action. The aim of this study was to examine the interaction of human serum albumin (HSA) with several polyamine analogues such as 1,3,7,11,7,11,15, in aqueous solution at physiological conditions, using a constant protein concentration and variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
135
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(147 citation statements)
references
References 39 publications
10
135
1
1
Order By: Relevance
“…The fluorescence enhancement is attributable to a combination of processes including enhanced absorption and modification of the decay rate of the molecule, and enhanced coupling efficiency of the fluorescent emission to the far field 23. As shown in Figure 4 A, the fluorescence intensity of hemoglobin increased with the addition of C‐GNRs, which was different from the previous findings that the protein fluorescence quenching occurred with the binding of nanomaterials 24, 25. When the fluorescence intensity at the maximum emission wavelength (334 nm) was evaluated, it was found that F 0 / F value (the ratio between the protein fluorescence intensity without and with the addition of C‐GNRs) was negatively linearly related with the incubation concentrations of C‐GNRs.…”
Section: Resultscontrasting
confidence: 91%
“…The fluorescence enhancement is attributable to a combination of processes including enhanced absorption and modification of the decay rate of the molecule, and enhanced coupling efficiency of the fluorescent emission to the far field 23. As shown in Figure 4 A, the fluorescence intensity of hemoglobin increased with the addition of C‐GNRs, which was different from the previous findings that the protein fluorescence quenching occurred with the binding of nanomaterials 24, 25. When the fluorescence intensity at the maximum emission wavelength (334 nm) was evaluated, it was found that F 0 / F value (the ratio between the protein fluorescence intensity without and with the addition of C‐GNRs) was negatively linearly related with the incubation concentrations of C‐GNRs.…”
Section: Resultscontrasting
confidence: 91%
“…2a and b). It binds various endogenous and exogenous ligands including hormones, fatty acids and foreign molecules such as drugs [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Recently our group has shown that HSA binds to BA with a binding constant of K BA = 1.685±0.01×10 6 M −1 [24].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the secondary structures of HSA and BSA and their drug complexes were carried out as reported [28,29]. The curvefitting analysis was performed using the GRAMS/AI Version 7.01 software of the Galactic Industries Corporation.…”
Section: Analysis Of Protein Secondary Structurementioning
confidence: 99%